Cover Picture: Electro‐Conductive Single‐Molecule Magnet Composed of a Dysprosium(III)‐Phthalocyaninato Double‐Decker Complex with Magnetoresistance (Angew. Chem. Int. Ed. 39/2021). Issue 39 (17th May 2021) - Sato, Tetsu; Breedlove, Brian K.; Yamashita, Masahiro; Katoh, Keiichi
Abstract : A one‐dimensional arrangement of single‐molecule magnets (SMMs), namely partially oxidized dysprosium(III) phthalocyaninato double‐decker complexes, [DyPc2 ]I x, was synthesized in the Communication by Keiichi Katoh, Masahiro Yamashita et al. on page 21179 by using electro‐oxidation and chemical oxidation. The results of spectrophotometric analysis on [DyPc2 ]I x are consistent with the Drude model, which theoretically explains the optical response of the metal. Since conductivity was observed at temperatures lower than the spin blocking temperature ( T B ), magnetoresistance (MR) effects observed as magnetic hysteresis were observed for the SMM. This strategy may pave the way for the construction of electro‐conductive SMMs as spin valves.